Evaluation of charging costs for various types of EVs in Malaysia - Abdul Kadir, Aida Fazliana; Sulaima, Mohamad Fani; Ab Aziz, Nur Hakimah; Mohd Zin, Ahmad Najmi; Shareef, Hussain; Rahman, Zulkifli Ab (2023)
The growing popularity of electric vehicles (EVs) has increased the demand for electric vehicle charging stations (EVCS) in power distribution systems. Numerous benefits can be obtained from integrating EVCS with the optimum charging power of various EVs, such as cost-effectiveness and time reduction. Therefore, this research aims to evaluate the charging cost and charging time for various types of EVs in Malaysia. In this paper, the charging cost and charging time for different EVs in Malaysia are compared and evaluated by considering the constant charging rate of the Battery Management System (BMS) relative to the battery’s capacity. The results highlight the significance of contemplating pricing structures and charging time reductions when selecting a charging provider. The evaluation provides valuable insights into the charging costs of EVs, thereby facilitating the identification of potential user bases and the estimation of charging needs for EVs in Malaysia.